Знахідки Euphorbia davidii Subils (Euphorbiaceae) на території Лівобережного Лісостепу України - Двірна, Т.С.; Звягінцева, К.О. (Український ботанічний журнал, 2013)
Приводятся сведения о новых локалитетах Euphorbia davidii Subils (Euphorbiaceae) на территории Левобережной Лесостепи Украины. В 2011—2012 гг. вид отмечен в г. Харькове и пгт Гребенка (Полтавская обл.), в последнем он образует значительные заросли. The information about new localities of Euphorbia davidii Subils in the Left-Bank Forest-Steppe zone of Ukraine is presented. New localities of the species were found in 2011—2012 along railways near Kharkiv city (Kharkiv Region) and Grebinka town (Poltava Region); in the latter site, the species had a large population.